2017
DOI: 10.1039/c7fo00439g
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of a non-aqueous self-double-emulsifying delivery system of rutin by fat crystals and nonionic surfactants: preparation and bioavailability study

Abstract: Literature examples of non-aqueous Pickering emulsions stabilized by fat crystals are very rare. Moreover, the applications of rutin are limited due to its low solubility in both water and oils (less than 0.10 mg g and 0.25 mg g, respectively). Thus, herein, we developed an optimum formulation of a non-aqueous self-double-emulsifying delivery system (SDEDS) containing rutin and evaluated its oral bioavailability. The new formulation stabilized by fat crystals (glycerol monostearate, GMS) and nonionic surfactan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 39 publications
1
16
0
Order By: Relevance
“…This study proposed a new method to improve the stability of double emulsions by the combination of oleogels and hydrogels. Compared to previous studies, this method could obtain stable double emulsions reinforced by oleogels with a low content of hydrophilic emulsifier and an applicable dispersibility (Wang et al, ; Zhao et al, ). Nonetheless, when employing this method, the composition of oleogels and hydrogels and technological parameter should be carefully investigated, because of the complex effects of solid lipids and alginate on double emulsions.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…This study proposed a new method to improve the stability of double emulsions by the combination of oleogels and hydrogels. Compared to previous studies, this method could obtain stable double emulsions reinforced by oleogels with a low content of hydrophilic emulsifier and an applicable dispersibility (Wang et al, ; Zhao et al, ). Nonetheless, when employing this method, the composition of oleogels and hydrogels and technological parameter should be carefully investigated, because of the complex effects of solid lipids and alginate on double emulsions.…”
Section: Resultsmentioning
confidence: 97%
“…In addition, lipid crystals could also improve the stability of primary emulsions through the Pickering effect as Pickering lipid crystals (Frasch‐Melnik, Spyropoulos, & Norton, ). It has been reported that GMS, which was an interfacially active emulsifier with a high melting point, was able to hinder the collision and the coalescence of droplets by creating crystal shells around the dispersed droplets (Ghosh & Rousseau, ; Wang et al, ). In general, the relative importance of these two roles was dependent on the presence of an appropriate emulsifier to facilitate the interfacial nucleation of solid lipids (Nadin et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The antioxidant activity of DMY and DMY‐loaded S‐SEDS was evaluated based on the ability to scavenge DPPH free radical according to the modified method reported by Wang, Huang, et al. (). Briefly, 100 µL of aqueous suspensions of DMY‐loaded S‐SEDS or DMY ethanol solution was mixed with 3.9 ml of DPPH ethanol solution (30 µg/ml).…”
Section: Methodsmentioning
confidence: 99%